2019
DOI: 10.1186/s12876-019-0993-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in patients under treatment for chronic hepatitis B in Ethiopia: a prospective cohort study

Abstract: Background Antiviral treatment for chronic hepatitis B (CHB) is largely unavailable in sub-Saharan Africa; hence, little is known about the prognosis after initiating treatment in African CHB patients. In this study we aimed to assess predictors of mortality in one of the largest CHB cohorts in sub-Saharan Africa. Methods Two-hundred-and-seventy-six CHB patients who started treatment with tenofovir disoproxil fumarate at a public hospital in Ethiopia between March 18, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Since HBV-and HCV-associated deaths are mainly due to chronic liver diseases, such as cirrhosis and liver cancer, we analyzed the mortality-associated risk factors in patients with chronic hepatitis infections. It is known that many risk factors are asso- ciated with chronic HBV, including male sex ( Si et al, 2019 ), advanced age, low BMI ( Desalegn et al, 2019 ), alcohol use, high alanine aminotransferase ( Zhou et al, 2020a ), and decompensated cirrhosis ( Desalegn et al, 2019 ). HCV-associated factors include male sex, advanced age, and lifestyle, such as smoking and drinking ( Nguyen et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since HBV-and HCV-associated deaths are mainly due to chronic liver diseases, such as cirrhosis and liver cancer, we analyzed the mortality-associated risk factors in patients with chronic hepatitis infections. It is known that many risk factors are asso- ciated with chronic HBV, including male sex ( Si et al, 2019 ), advanced age, low BMI ( Desalegn et al, 2019 ), alcohol use, high alanine aminotransferase ( Zhou et al, 2020a ), and decompensated cirrhosis ( Desalegn et al, 2019 ). HCV-associated factors include male sex, advanced age, and lifestyle, such as smoking and drinking ( Nguyen et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cohorts represented by HEPSANET group members were described in 21 articles. 11,13,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] We contacted corresponding authors from the remaining 3 articles, [43][44][45] and all authors agreed to contribute individual patient data. We additionally included unpublished data from three sites (Cape Town, South Africa; Thiès, Senegal; and Dakar, Senegal) and data from one additional study published since the search was conducted from Malawi.…”
Section: Resultsmentioning
confidence: 99%
“…The gene-gene multiplicative interaction was evaluated by Logistic Regression model. The additive interaction analysis was carried out jointly by SPSS21.0 and Excel (2019). Firstly, calculate B, P, OR (95%CI) and covariance matrix with SPSS21.0.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with the results of other research teams. Studies have shown that HBV susceptibility factors include gender (male) ( Si et al, 2019 ) and advanced age ( Desalegn et al, 2019 ). In addition, smoking may increase susceptibility to HBV-HCC by affecting viral load ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%